EFEK MODERASI FIRM SIZE TERHADAP FAKTOR YANG MEMPENGARUHI PROFIT GROWTH - Lia Dwi Martika; Syahrul Syarifudin; Yudi Febriansyah (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
Abstract. The aim of this research is to produce empirical facts/models that can explain the factors that influence profit growth with firm size as a moderating variable. To test the hypothesis that has been formulated through proof to test the research hypothesis with statistical calculations so that proof results can be obtained that show the hypothesis is rejected or accepted. In this research, researchers conducted research on Manufacturing Companies in the Consumer Goods Industry Sector in 2018-2022. The F test results show that debt to equity ratio, total asset turnover, return on assets, net profit margin and operating cash flow together influence profit growth. The t test results show that the debt to equity ratio has a significant negative effect on profit growth, return on assets, total asset turnover and net profit margin have a significant positive effect on profit growth and operating cash flow has no effect on profit growth, firm size moderates and strengthens the relationship between total assets turnover and net profit margin with profit growth, firm size moderates and weakens the relationship between debt to equity ratio and profit growth, firm does not moderate the relationship between return on assets and operating cash flow with profit growth.